An examination of factors hindering the growth of media firms in Capricorn District region of Limpopo Province, South Africa - Maswanganyi, F. T.; Nkoana, E. M. (My University, 2016)
All firms operate within the challenging macro- and micro-economic factors and internal and external environments. Media firms experience additional challenges from disruptive innovation. With this background, this article reports on a qualitative study that examined factors that hinder the growth of media firms operating in the Capricorn District of Limpopo Province, South Africa. Empirical data was collected by administering an interview guide through face-to-face interviewing with Chief Executives of media firms (n=20). Primary data obtained from the interviews was analysed using Qualitative Content Analysis (QCA). The researchers found that the main barriers of growth of media firms in Capricorn District are associated with political interference, sexual advances, and lack of financial capital.
Published in: Journal of Public Administration and Development Alternatives Vol. 1 No.1 July 2016, 90 -101
Keywords: Media firms - Limpopo - South Africa; Media industry - South Africa